NCERT Solutions For Class 12 Maths Chapter 2 Exercise 2.1

Go back to  'Inverse Trigonometric Functions'

Chapter 2 Ex.2.1 Question 1

Find the principal value of \({\sin ^{ - 1}}\left( { - \frac{1}{2}} \right)\).

Solution

Let, \({\sin ^{ - 1}}\left( { - \frac{1}{2}} \right) = y\)

Hence,

\[\begin{align}\sin y &= \left( { - \frac{1}{2}} \right)\\&= - \sin \left( {\frac{\pi }{6}} \right)\\&= \sin \left( { - \frac{\pi }{6}} \right)\end{align}\]

Range of the principal value of \({\sin ^{ - 1}}\left( x \right)\) is \(\left( { - \frac{\pi }{2},\frac{\pi }{2}} \right)\)

Thus, principal value of \({\sin ^{ - 1}}\left( { - \frac{1}{2}} \right) = \left( { - \frac{\pi }{6}} \right)\).

Chapter 2 Ex.2.1 Question 2

Find the principal value of \({\cos ^{ - 1}}\left( {\frac{{\sqrt 3 }}{2}} \right)\).

Solution

Let, \({\cos ^{ - 1}}\left( {\frac{{\sqrt 3 }}{2}} \right) = y\)

Hence,

\[\begin{align}\cos y &= \left( {\frac{{\sqrt 3 }}{2}} \right)\\&= \cos \frac{\pi }{6}\end{align}\]

Range of the principal value of \({\cos ^{ - 1}}\left( x \right)\) is \(\left( {0,\pi } \right)\).

Thus, principal value of \({\cos ^{ - 1}}\left( {\frac{{\sqrt 3 }}{2}} \right) = \left( {\frac{\pi }{6}} \right)\)

Chapter 2 Ex.2.1 Question 3

Find the principal value of \(\ {\rm{cosec}}{^{ - 1}}\left( 2 \right)\).

Solution

Let, \(\ {\rm{cosec}}^{ - 1}\left( 2 \right) = y\)

Hence,

\[\begin{align}\ {\rm{cosec}}\,y &= 2\\ &= {\rm{cosec}}\left( {\frac{\pi }{6}} \right)\end{align}\]

Range of the principal value of \(\ {\rm{cosec}}{^{ - 1}}\left( x \right) = \left[ { - \frac{\pi }{2},\frac{\pi }{2}} \right] - \left\{ 0 \right\}\)

Thus, principal value of \(\ {\rm{cosec}}{^{ - 1}}\left( 2 \right) = \left( {\frac{\pi }{6}} \right)\).

Chapter 2 Ex.2.1 Question 4

Find the principal value of \({\tan ^{ - 1}}\left( { - \sqrt 3 } \right)\)

Solution

Let, \({\tan ^{ - 1}}\left( { - \sqrt 3 } \right) = y\)

Hence,

\[\begin{align}\tan y &= - \sqrt 3 \\&= - \tan \left( {\frac{\pi }{3}} \right)\\&= \tan \left( { - \frac{\pi }{3}} \right)\end{align}\]

Range of the principal value of \({\tan ^{ - 1}}\left( x \right) = \left( { - \frac{\pi }{2},\frac{\pi }{2}} \right)\)

Thus, principal value of \({\tan ^{ - 1}}\left( { - \sqrt 3 } \right) = \left( { - \frac{\pi }{3}} \right)\).

Chapter 2 Ex.2.1 Question 5

Find the principal value of \({\cos ^{ - 1}}\left( { - \frac{1}{2}} \right)\)

Solution

Let, \({\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) = y\)

Hence,

\[\begin{align}\cos y &= - \frac{1}{2}\\&= - \cos \left( {\frac{\pi }{3}} \right)\\&= \cos \left( {\pi - \frac{\pi }{3}} \right)\\&= \cos \left( {\frac{{2\pi }}{3}} \right)\end{align}\]

Range of the principal value of \({\cos ^{ - 1}}\left( x \right) = \left[ {0,\pi } \right]\)

Thus, principal value of \({\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) = \left( {\frac{{2\pi }}{3}} \right)\).

Chapter 2 Ex.2.1 Question 6

Find the principal value of \({\tan ^{ - 1}}\left( { - 1} \right)\)

Solution

Let, \({\tan ^{ - 1}}\left( { - 1} \right) = y\)

Hence,

\[\begin{align}\tan {\rm{ }}y &= - 1\\&= - \tan \left( {\frac{\pi }{4}} \right)\\&= \tan \left( { - \frac{\pi }{4}} \right)\end{align}\]

Range of the principal value of \({\tan ^{ - 1}}\left( x \right) = \left( { - \frac{\pi }{2},\frac{\pi }{2}} \right)\)

Thus, principal value of \({\tan ^{ - 1}}\left( { - 1} \right) = \left( { - \frac{\pi }{4}} \right)\).

Chapter 2 Ex.2.1 Question 7

Find the principal value of \({\sec ^{ - 1}}\left( {\frac{2}{{\sqrt 3 }}} \right)\)

Solution

Let, \({\sec ^{ - 1}}\left( {\frac{2}{{\sqrt 3 }}} \right)=y \)

Hence,

\[\begin{align} \sec \;y &= \frac{2}{{\sqrt 3 }} \\ &= \sec \left( {\frac{\pi }{6}} \right) \end{align} \]

Range of the principal value of \({\sec ^{ - 1}}\left( x \right) = \left[ {0,\pi } \right] - \left\{ {\frac{\pi }{2}} \right\}\)

Thus, principal value of \({\sec ^{ - 1}}\left( {\frac{2}{{\sqrt 3 }}} \right) = \left( {\frac{\pi }{6}} \right)\).

Chapter 2 Ex.2.1 Question 8

Find the principal value of \({\cot ^{ - 1}}\left( {\sqrt 3 } \right)\)

Solution

Let, \({\cot ^{ - 1}}\left( {\sqrt 3 } \right) = y\)

Hence,

\[\begin{align}\cot \;y &= \sqrt 3 \\&= \cot \left( {\frac{\pi }{6}} \right)\end{align}\]

Range of the principal value of \({\cot ^{ - 1}}\left( x \right) = \left( {0,\pi } \right)\)

Thus, principal value of \({\cot ^{ - 1}}\left( {\sqrt 3 } \right) = \left( {\frac{\pi }{6}} \right)\).

Chapter 2 Ex.2.1 Question 9

Find the principal value of \({\cos ^{ - 1}}\left( { - \frac{1}{{\sqrt 2 }}} \right)\)

Solution

Let, \({\cos ^{ - 1}}\left( { - \frac{1}{{\sqrt 2 }}} \right) = y\)

Hence,

\[\begin{align}\cos \;y &= - \frac{1}{{\sqrt 2 }}\\&= - \cos \left( {\frac{\pi }{4}} \right)\\&= \cos \left( { - \frac{\pi }{4}} \right)\\&= \cos \left( {\pi - \frac{\pi }{4}} \right)\\&= \cos \left( {\frac{{3\pi }}{4}} \right)\end{align}\]

Range of the principal value of \({\cos ^{ - 1}}\left( x \right) = \left[ {0,\pi } \right]\)

Thus, principal value of \({\cos ^{ - 1}}\left( { - \frac{1}{{\sqrt 2 }}} \right) = \left( {\frac{{3\pi }}{4}} \right)\).

Chapter 2 Ex.2.1 Question 10

Find the principal value of \({\rm{cose}}{{\rm{c}}^{ - 1}}\left( { - \sqrt 2 } \right)\)

Solution

Let, \({\rm{cose}}{{\rm{c}}^{ - 1}}\left( { - \sqrt 2 } \right) = y\)

Hence,

\[\begin{align}{\rm{cosec }}\;y &= - \sqrt 2 \\&= - {\rm{cosec}}\left( {\frac{\pi }{4}} \right)\\&= {\rm{cosec}}\left( { - \frac{\pi }{4}} \right)\end{align}\]

Range of the principal value of \({\rm{cose}}{{\rm{c}}^{ - 1}}\left( x \right) = \left[ { - \frac{\pi }{2},\frac{\pi }{2}} \right] - \left\{ 0 \right\}\)

Thus, principal value of \({\rm{cose}}{{\rm{c}}^{ - 1}}\left( { - \sqrt 2 } \right) = \left( { - \frac{\pi }{4}} \right)\).

Chapter 2 Ex.2.1 Question 11

Find the value of \({\tan ^{ - 1}}\left( 1 \right) + {\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) + {\sin ^{ - 1}}\left( { - \frac{1}{2}} \right)\).

Solution

Let, \({\tan ^{ - 1}}\left( 1 \right) = x\)

Hence,

\[\begin{align}\tan x &= 1\\&= \tan \left( {\frac{\pi }{4}} \right)\end{align}\]

Therefore,

\({\tan ^{ - 1}}\left( 1 \right) = \left( {\frac{\pi }{4}} \right)\)

Now, let \({\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) = y\)

Hence,

\[\begin{align}\cos y &= - \frac{1}{2}\\&= - \cos \left( {\frac{\pi }{3}} \right)\\&= \cos \left( {\pi - \frac{\pi }{3}} \right)\\&= \cos \left( {\frac{{2\pi }}{3}} \right)\end{align}\]

Therefore,

\({\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) = \frac{{2\pi }}{3}\)

Again, let \({\sin ^{ - 1}}\left( { - \frac{1}{2}} \right) = z\)

Hence,

\[\begin{align}\sin z &= - \frac{1}{2}\\&= - \sin \left( {\frac{\pi }{6}} \right)\\&= \sin \left( { - \frac{\pi }{6}} \right)\end{align}\]

Therefore,

\({\sin ^{ - 1}}\left( { - \frac{1}{2}} \right) = - \frac{\pi }{6}\)

Thus,

\[\begin{align}{\tan ^{ - 1}}\left( 1 \right) + {\cos ^{ - 1}}\left( { - \frac{1}{2}} \right) + {\sin ^{ - 1}}\left( { - \frac{1}{2}} \right) &= \frac{\pi }{4} + \frac{{2\pi }}{3} - \frac{\pi }{6}\\&= \frac{{3\pi + 8\pi - 2\pi }}{{12}}\\&= \frac{{9\pi }}{{12}}\\&= \frac{{3\pi }}{4}\end{align}\]

Chapter 2 Ex.2.1 Question 12

Find the value of \({\cos ^{ - 1}}\left( {\frac{1}{2}} \right) + 2{\sin ^{ - 1}}\left( {\frac{1}{2}} \right)\)

Solution

Let, \({\tan ^{ - 1}}\left( 1 \right) = x\)

Hence,

\[\begin{align}\cos x &= \frac{1}{2}\\&= \cos \left( {\frac{\pi }{3}} \right)\end{align}\]

Therefore,

\({\cos ^{ - 1}}\left( {\frac{1}{2}} \right) = \frac{\pi }{3}\)

Let, \({\sin ^{ - 1}}\left( {\frac{1}{2}} \right) = y\)

Hence,

\[\begin{align}\sin y &= \frac{1}{2}\\&= \sin \left( {\frac{\pi }{6}} \right)\end{align}\]

Therefore,

\({\sin ^{ - 1}}\left( {\frac{1}{2}} \right) = \frac{\pi }{6}\)

Thus

\[\begin{align}{\cos ^{ - 1}}\left( {\frac{1}{2}} \right) + 2{\sin ^{ - 1}}\left( {\frac{1}{2}} \right) &= \frac{\pi }{3} + 2\left( {\frac{\pi }{6}} \right)\\&= \frac{{2\pi }}{3}\end{align}\]

Chapter 2 Ex.2.1 Question 13

Find the value of \({\sin ^{ - 1}}x = y\), then

(A) \(0 \le y \le \pi \)

(B) \( - \frac{\pi }{2} \le y \le \frac{\pi }{2}\)

(C) \(0 \le y \le \pi \)

(D) \( - \frac{\pi }{2} < y < \frac{\pi }{2}\)

Solution

It is given that \({\sin ^{ - 1}}x = y\)

Range of the principal value of \({\sin ^{ - 1}}x = \left[ { - \frac{\pi }{2},\frac{\pi }{2}} \right]\)

Thus, \( - \frac{\pi }{2} \le y \le \frac{\pi }{2}\)

The answer is B.

Chapter 2 Ex.2.1 Question 14

Find the value of \({\tan ^{ - 1}}\sqrt 3 - {\sec ^{ - 1}}\left( { - 2} \right)\)is equal to

(A) \(0\)

(B) \( - \frac{\pi }{3}\)

(C) \(\frac{\pi }{3}\)

(D) \(\frac{{2\pi }}{3}\)

Solution

Let

Hence,

\[\begin{align}\tan x &= \sqrt 3 \\&= \tan \left( {\frac{\pi }{3}} \right)\end{align}\]

Range of the principal value of \({\tan ^{ - 1}}x = \left( { - \frac{\pi }{2},\frac{\pi }{2}} \right)\)

Therefore,\({\tan ^{ - 1}}\left( {\sqrt 3 } \right) = \left( {\frac{\pi }{3}} \right)\)

Let \({\sec ^{ - 1}}\left( { - 2} \right) = y\)

Hence,

\[\begin{align}\sec y &= \left( { - 2} \right)\\&= - \sec \left( {\frac{\pi }{3}} \right)\\&= \sec \left( { - \frac{\pi }{3}} \right)\\&= \sec \left( {\pi - \frac{\pi }{3}} \right)\\&= \sec \left( {\frac{{2\pi }}{3}} \right)\end{align}\]

Range of the principal value of \({\rm{se}}{{\rm{c}}^{ - 1}}{\rm{x = }}\left[ {0,\pi } \right] - \left\{ {\frac{\pi }{2}} \right\}\)

Therefore, \({\sec ^{ - 1}}\left( { - 2} \right) = \frac{{2\pi }}{3}\)

Thus,

\[\begin{align}{\tan ^{ - 1}}\sqrt 3 - {\sec ^{ - 1}}\left( { - 2} \right)& = \frac{\pi }{3} - \frac{{2\pi }}{3}\\&= - \frac{\pi }{3}\end{align}\]

The answer is \(B\).

  
Download Cuemath NCERT App
Related Sections
Related Sections

Learn from the best math teachers and top your exams

Learn from the best

math teachers and top

your exams


Personalized Curriculum
Instant Doubts clarification
Cover latest CBSE Syllabus
Unlimited Mock & Practice tests
Covers CBSE, ICSE, IB curriculum

Instant doubt clearing with Cuemath Advanced Math Program
0